Hydrothermal carbonization of primary sewage sludge and synthetic faeces: Effect of reaction temperature and time on filterability. Issue 5 (6th April 2015) - Danso‐Boateng, Eric; Holdich, Richard G.; Wheatley, Andrew D.; Martin, Simon J.; Shama, Gilbert
Abstract : The effect of reaction temperature and time on the filterability of slurries of primary sewage sludge (PSS) and synthetic faeces (SF) following hydrothermal carbonization (HTC) was investigated and optimized using response surface methodology (RSM). Filterability was shown to improve as the treatment temperature and reaction time at which the solids were carbonized was increased. The best filtration results were achieved at the highest temperature (200°C) and longest treatment time (240 min) employed here. The specific cake resistance to filtration of the carbonized solids was found to vary between 5.43 × 10 12 and 2.05 × 10 10 m kg −1 for cold filtration of PSS, 1.11 × 10 12 and 3.49 × 10 10 m kg −1 for cold filtration of SF, and 3.01 × 10 12 and 3.86 × 10 10 m kg −1 for hot filtration of SF, and decreased with increasing reaction temperature and time for carbonization. There was no significant difference in the specific resistance of cold and hot filtration for SF. The RSM models employed here were found to yield predictions that were close to the experimental results obtained and should therefore prove useful in designing and optimizing HTC filtration systems for generating solids for a wide variety of end uses. © 2015 American Institute of Chemical Engineers Environ Prog, 34: 1279–1290, 2015